Prevalence of Pelvic Organ Prolapse in a Tertiary Care Hospital of Nepal - Neupane, Bibhushan; Malla, Rosy Vaidya; Khadka, Sabina; Karki, Sagun; Khadka, Manita; Adhikari , Kabita; Acharya, Manisha (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Pelvic organ prolapse is the descent of the pelvic organ from its normal position. Although few genetic and idiopathic causes have been associated with it, it most commonly follows difficult and repeated child births, making it one of the most common morbidities in developing countries like Nepal. In this study, we aim to find the prevalence of pelvic organ prolapse. Methods: A retrospective study was carried out from June 2020 to June 2022 in inpatient setting of Shree Birendra Hospital (SBH), Nepalese Army Institute of Health Sciences (NAIHS), Kathmandu, Nepal. We used systemic random sampling method to select the participants and collected data from hospital records. Descriptive statistics were used to find the prevalence of pelvic organ prolapse, types, grades and the surgery performed. Results: Out of 391 admitted for gynaecological surgeries, 17 of them had pelvic organ prolapse (4.35%). Among them, 13 had grade III and four of them had grade II uterovaginal (UV) prolapse. Vaginal hysterectomy with pelvic floor repair was the most common surgery performed in pelvic organ prolapse. Conclusions: Our study showed 4.35% prevalence of pelvic organ prolapse in our centre.